An exploratory bibliometric analysis of research on Blue Ocean Strategy. (16th September 2022) - Madsen, Dag Øivind; Slåtten, Kåre
Blue Ocean Strategy is a strategy concept that was introduced during the mid-2000s. Although the concept has received much attention in the business world, it has to a large extent been ignored by strategy and management scholars. This paper carries out an exploratory bibliometric analysis of research on Blue Ocean Strategy, intending to identify the most influential journals, documents, authors, and countries. The paper provides a preliminary overview of the current state of research on Blue Ocean Strategy and can thus serve as a starting point for more in-depth analyses. It also provides a reading list for researchers, students, and practitioners new to the concept of Blue Ocean Strategy.